Progress and outlook of solid oxide fuel cell technology for stationary power generation applications - Le, Duc-Dung; Nguyen, Huu-Linh; Yu, Sangseok; Le, Hoang Hiep; Hoang, Tuan-Dung (Frontiers in Energy Research, 2025)
Solid oxide fuel cells (SOFCs) are among the most promising electrochemical technologies for high-efficiency, low-emission power generation. This review provides a comprehensive overview of recent advances in SOFC materials, system architectures, and commercialization pathways, with emphasis on intermediate-temperature operation to enhance durability and reduce costs. Developments in electrolyte materials are analyzed alongside progress in anode and cathode advances in materials. At the system level, the manuscript compares electrolyte-supported and anode-supported configurations, examines sealing technologies and thermal cycling durability in planar stacks, and discusses fuel preparation strategies with emphasis on sulfur removal from hydrocarbon fuels. The integration of direct internal reforming (DIR) SOFC systems and the role of anode gas recycle in improving efficiency and thermal management are also addressed. The high-temperature exhaust from SOFCs supports cogeneration and trigeneration applications, enabling additional power or heating/cooling through thermodynamic cycles such as Rankine and Brayton, thereby enhancing overall system efficiency. Finally, the review examines the status of commercial SOFC deployment, presenting case studies of leading industrial players such as Bloom Energy (USA), Ceres Power (UK), and SolydEra (Italy). The paper concludes with an assessment of the key challenges and perspectives for SOFC commercialization in stationary power generation, including cost reduction, stack lifetime extension, large-scale manufacturing, and system integration strategies required to achieve widespread market adoption.